Test the Effectiveness of Soursop Leaf Extract and Tapak Dara Leaf Extract as Mosquito Larvicide - Syifa Zulfiani Zakiyah Susilo; Aminah Asngad (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
In this rainy season the risk of contracting Dengue Fever increases. Many people control dengue fever chemically. The use of chemical larvicides has many disadvantages such as environmental pollution, resistance, and negative impacts on human health. This research aims to develop a natural larvicide from extracts of soursop leaves (Annona muricata) and tapak dara leaves (Catharanthus roseus). The study used a completely randomized design, with three replications. Soursop leaf and tapak dara leaf extracts were extracted using a maceration process using 70% ethanol solvent. III-IV instar Aedes aegypti mosquito larvae were used during the experiment, to assess the effect of formula (3 levels), dose (3 levels), and exposure time for 12 hours. All data were analyzed using Two-way ANOVA. The research results showed that the F1 formula and D3 dose were effective in eradicating mosquito larvae. Where the higher the concentration of soursop leaf extract and the higher the dose, the higher the mortality of mosquito larvae.